Visual analytics of COVID-19 dissemination in São Paulo state, Brazil - Marcílio-Jr, Wilson E. [UNESP]; Eler, Danilo M. [UNESP]; Garcia, Rogério E. [UNESP]; Correia, Ronaldo C.M. [UNESP]; Rodrigues, Rafael M.B. [UNESP] (Elsevier, 2021)
Visual analytics techniques are useful tools to support decision-making and cope with increasing data, particularly to monitor natural or artificial phenomena. When monitoring disease progression, visual analytics approaches help decision-makers to understand or even prevent dissemination paths. In this paper, we propose a new visual analytics tool for monitoring COVID-19 dissemination. We use k-nearest neighbors of cities to mimic neighboring cities and analyze COVID-19 dissemination based on comparing a city under consideration and its neighborhood. Moreover, such analysis is performed within periods, which facilitates the assessment of isolation policies. We validate our tool by analyzing the progression of COVID-19 in neighboring cities of São Paulo state, Brazil.
Keywords: COVID-19; Risk assessment; Visual analytics